Synthesis, Antibacterial and Antioxidant Evaluation of 2-Substituted-4-arylidene-5(4H)-oxazolone Derivatives - Lina Saadi; Shaimaa Adnan (Universitas Gadjah Mada, 2023)
In this research, the synthesis of new substituted oxazolone derivatives is described via Erlenmeyer synthesis of N-acyl amino acid. Firstly, the azo derivative 1 was prepared by coupling the diazonium salt of 3-amino-4-methoxybenzoic acid with 4,5-dichloroimidazole in sodium hydroxide solution. Benzoyl chloride derivative 2, the key intermediate of the synthesis, was synthesized by the acylation of azo-carboxylic acid derivative 1 with thionyl chloride. The resulting acyl chloride derivative reacted with glycine in a basic catalyst to form a hippuric acid derivative 3. After that, oxazolone derivatives 4a–4f were prepared via the reaction of the hippuric acid derivative with various aromatic aldehydes. All new compound structures were confirmed by spectral techniques, i.e., FTIR, 1H-NMR, 13C-NMR spectroscopy, and elemental analysis. The antimicrobial activity (Staphylococcus aureus and Escherichia coli) of all new compounds was screened in vitro. The results against S. aureus and E. coli showed that most of the tested compounds have an activity ranging from moderate to low. The antioxidant activity of derivative 4a was also evaluated and showed good antioxidant activity.